1982
DOI: 10.1111/j.1600-0447.1982.tb00913.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus (HSV) antibodies in child psychiatric patients and normal children

Abstract: The prevalence of herpes simplex virus (HSV) antibodies has been investigated in 123 child psychiatric patients and 86 normal children. HSV antibodies were measured by ELISA technique. The prevalence of HSV antibodies in different diagnostic groups (conduct disorder, emotional disorder, hyperkinetic syndrome, anorexia nervosa, infantile autism and borderline schizophrenia in childhood) was compared with age-matched normal children, but no significant differences were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 9 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Moreover, cellmediated immunity (CMI) to HSV, investigated by in psychotic depression, was found similar to that observed after acute HSV infection or recurrence. On the other hand, antibodies to HSV were not found significantly higher in hospitalized psychiatric children than in normal ones (Jorgensen et al, 1982).…”
Section: Introductionmentioning
confidence: 62%
“…Moreover, cellmediated immunity (CMI) to HSV, investigated by in psychotic depression, was found similar to that observed after acute HSV infection or recurrence. On the other hand, antibodies to HSV were not found significantly higher in hospitalized psychiatric children than in normal ones (Jorgensen et al, 1982).…”
Section: Introductionmentioning
confidence: 62%
“…It is also reported that patients that are diagnosed with autism spectrum disorders (ASD) are observed to have HSV-1 infection (Ghaziuddin, Tsai, Eilers, & Ghaziuddin, 1992;Gillberg, 1986). A few reports also confirmed the occurrence of antibodies to HSV in children diagnosed with ASD, but the conflict is observed in final outcomes (Jörgensen, Vejlsgaard Goldschmidt, & Vestergaard, 1982;Mora et al, 2009). The infection can be life-threatening in case of aged patients, immune-compromised persons, neonates, transplant patients under immune suppression, and patients with acquired immune deficiency syndrome (Brezáni et al, 2018).…”
Section: Introductionmentioning
confidence: 98%